RESPONSE OF INFLAMMATORY CYSTOID MACULAR EDEMA TO TREATMENT USING ORAL ACETAZOLAMIDE. Issue 5 (May 2019) - Pepple, Kathryn L.; Nguyen, Macklin H.; Pakzad-Vaezi, Kaivon; Williamson, Kathleen; Odell, Naomi; Lee, Cecilia; Leveque, Thellea K.; Van Gelder, Russell N.
Abstract : Purpose: To determine the treatment effect of oral acetazolamide on refractory inflammatory macular edema. Methods: A retrospective review of identified patients with uveitic or pseudophakic macular edema treated using acetazolamide between 2007 and 2014. Visual acuity and central macular subfield thickness was determined at baseline and at first follow-up. Baseline optical coherence tomography features were analyzed as predictors of acetazolamide response. Results: Sixteen patients (19 eyes) of 61 screened met all criteria. Mean age was 57.9 years (19.7–81.1). The most common diagnosis was idiopathic uveitis (n = 6, 31.6%). Mean uveitis duration was 4.4 years (0.2–27.5). Average central macular subfield thickness decreased significantly (from 471.8 ± 110.6 μ m to 358.3 ± 50.4 μ m) ( P < 0.0001). Average visual acuity (logarithm of the minimum angle of resolution) improved significantly from 20/54 (0.43 ± 0.25) to 20/37 (0.27 ± 0.16) ( P = 0.003). Pretreatment optical coherence tomographies demonstrated intraretinal fluid (n = 19, 100%), subretinal fluid (n = 8, 42.1%), epiretinal membrane (n = 13, 68.3%), and vitreomacular traction (n = 1, 5.2%). No optical coherence tomography characteristic was predictive of a response to therapy. Conclusion: There is a significant benefit to vision and central macular subfield thickness after acetazolamide treatment in patients with inflammatory macular edema. In patients with refractory inflammatory macular edema, treatment using acetazolamide can provide anatomical and visual benefit without corticosteroid-related adverse effects. Abstract : Addition of acetazolamide therapy to the treatment of uveitic macular edema can provide a significant improvement in macular thickness and visual acuity at first follow-up when compared with baseline.